A Study of the Perception of Outsourced Security Guards (Satpam) in the Jabodetabek Area Regarding Job Security - Langit, Putri Sangga; Nasution, Yasmine (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Job security is a crucial aspect of employment, especially for outsourced security guards (Satpam) in Jabodetabek, who face numerous challenges due to their contractual status. This study aims to explore the perceptions, importance, challenges, and root causes of job security issues in this sector. Using a qualitative approach, semi-structured interviews were conducted with outsourced Satpam, employees of security service companies (BUJP; Badan Usaha Jasa Pengamanan), and users’ employees. Data were analyzed using thematic analysis. The results reveal six key elements of job security: benefits, salary, relationships with supervisors, work environment, career development, and job stability. Challenges include unfulfilled benefits, salary discrepancies, hazardous work environments, and job instability. Root causes are linked to poor BUJP management, weak contractual agreements, and limited regulatory enforcement. The study concludes with recommendations for regulatory reform, improved collaboration among stakeholders, and targeted training programs to enhance job security and professional growth.